2008
DOI: 10.1177/104063870802000325
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Feline Leukemia Virus in the Endangered Iberian Lynx (Lynx Pardinus)

Abstract: Abstract. Feline retroviruses are rarely reported in lynx species. Twenty-one Iberian lynx (Lynx pardinus) blood and tissue samples collected from Doñ ana National Park and Los Villares (Sierra Morena) in southern Spain during 1993-2003 were analyzed by polymerase chain reaction to amplify nucleic acids from feline retroviruses. Six samples were positive for Feline leukemia virus (FeLV), but no samples tested positive for Feline immunodeficiency virus. The BLAST analysis indicated that 5 of the 6 sequences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Histopathological studies revealed generalized immune depletion in these animals, apparently unrelated to infectious agents or malnutrition [24], and glomerulonephritis [28]. Furthermore, the presence of feline leukemia virus (FeLV) provirus was recently reported in six samples originating from both the Doñ ana and Sierra Morena areas in southern Spain between 1994 and 2003 [29].…”
Section: Introductionmentioning
confidence: 93%
“…Histopathological studies revealed generalized immune depletion in these animals, apparently unrelated to infectious agents or malnutrition [24], and glomerulonephritis [28]. Furthermore, the presence of feline leukemia virus (FeLV) provirus was recently reported in six samples originating from both the Doñ ana and Sierra Morena areas in southern Spain between 1994 and 2003 [29].…”
Section: Introductionmentioning
confidence: 93%
“…Feral cats 6,7 or endangered wild felids as linx and panthers 8 are also under risk of FeLV infection. Both retroviruses affect the immune system and are causes of significant morbidity and mortality 9 or predispose to infections such as hemotropic mycoplasmas 10 or feline infectious peritonitis 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published retrospective study (Luaces et al, 2008), six of 21 lynxes sampled between 1993 and 2003 were found to be FeLV provirus-positive in Doñ ana and Sierra Morena areas, but not antigenemic. Although no clinical data were reported in this study, there was no indication that FeLV infection could represent a major risk for the lynx populations.…”
Section: Prospective Of the Susceptibility Of Iberian Lynx To Future mentioning
confidence: 95%
“…Chlamydophila felis and several parasitic diseases in captive and wild individuals (Briones et al, 2000;Vicente et al, 2004;Luaces et al, 2005;Millá n et al, 2007Millá n et al, , 2009Sobrino et al, 2007;Willi et al, 2007;Meli et al, 2009). Occasional exposure to viral infections such as feline herpes virus (FHV), feline calicivirus (FCV), feline parvovirus (FPV), canine distemper virus (CDV) and feline leukemia virus (FeLV) may occur (Luaces et al, 2008;Millá n et al, 2009;Roelke et al, 2008;Meli et al, 2009). Recently, a severe FeLV epidemic struck two small subpopulations of the Doñ ana area.…”
mentioning
confidence: 99%